Inspiring elite action for a more just society? : media framing of elite social responsibility in an unequal, unconsolidated democracy : a case study from Namibia - Virmasalo, Veera (2017)
Tutkimus keskittyi Namibiaan, joka on yksi maailman epätasa-arvoisimmista maista.